2014
DOI: 10.1177/0004867414550210
|View full text |Cite
|
Sign up to set email alerts
|

Valproate for management of idiopathic olfactory hallucinosis

Abstract: John's behavioural and affective changes, first diagnosed as a primary mood disorder, were then attributed to a head injury, supported by an abnormal CT. The case highlights two important principles: first, the importance of a detailed history, which revealed that the behavioural and cognitive changes had occurred years after the head injury, and second, the utility of MRI compared with non-contrast CT. FundingThis research received no specific grant from any funding agency in the public, commercial or not-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Hallucinations are not uncommonly seen in bipolar disorder, with a recent study finding that as many as 41.4% of bipolar disorder patients had hallucinations (in any modality) and 8.1% had olfactory hallucinations (Lewandowski et al, 2009). The mechanism of olfactory hallucinations remains unclear, although many mechanisms, including reverberating neuronal circuits, have been proposed (Chauhan et al, 2014). It is well known that the early identification of prodromal symptoms and prompt treatment can successfully delay the relapse of bipolar disorder (Perry et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Hallucinations are not uncommonly seen in bipolar disorder, with a recent study finding that as many as 41.4% of bipolar disorder patients had hallucinations (in any modality) and 8.1% had olfactory hallucinations (Lewandowski et al, 2009). The mechanism of olfactory hallucinations remains unclear, although many mechanisms, including reverberating neuronal circuits, have been proposed (Chauhan et al, 2014). It is well known that the early identification of prodromal symptoms and prompt treatment can successfully delay the relapse of bipolar disorder (Perry et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Medications used included topiramate, nortriptyline, amitriptyline, flunarizine, propranolol, lamotrigine, verapamil, Petasites hybridus root extract and magnesium oxide. Literature review of cases reported improvements with indomethacin, gabapentin, phenytoin, sodium valproate, oral alpha‐lipoic acid and supraorbital and occipital neurostimulation . Surgical therapies tried included bifrontal craniotomy to remove olfactory bulbs and endoscopic trans/intranasal procedure to excise the olfactory epithelium .…”
Section: Case Historiesmentioning
confidence: 99%
“…Literature review of cases reported improvements with indomethacin, gabapentin, phenytoin, sodium valproate, oral alpha-lipoic acid and supraorbital and occipital neurostimulation. 5,27,30,79 Surgical therapies tried included bifrontal craniotomy to remove olfactory bulbs and endoscopic trans/intranasal procedure to excise the olfactory epithelium. 4,5 The majority of patients with olfactory hallucinations with no clear cause found improvement over time without specific treatments.…”
Section: Case Historiesmentioning
confidence: 99%